3D coupled FEM-IBIEM for non-linear seismic response of a sedimentary basin using equivalent-linearized soil model. (October 2022) - Liu, Zhong-xian; Sun, Jun; Meng, Si-bo; Feng, Ting; Huang, Lei; Li, Hu
Abstract: Based on an equivalent-linearized dynamic constitutive model of the soil, the coupled finite element method - indirect boundary integral equation method (FEM-IBIEM) is developed to carry out the non-linear seismic response of a three-dimensional (3-D) sedimentary basin. The indirect boundary integral equation method (IBIEM), which can significantly reduce the solution dimension, is employed to solve the exterior response of the sedimentary basin. Due to the inhomogeneity and nonlinearity of the soft soil, the finite element method (FEM) is used to analyze the response of the sedimentary basin. Based on the verification of numerical accuracy, the scattering issue in a sedimentary basin with linearly varying shear wave velocity under incident P and SV waves is investigated. Numerical results show that: the coherence effect increases with the increase of the incident frequency, and the amplification of surface displacement and acceleration is distinct. Due to the soil-nonlinearity, the peak ground acceleration (PGA) at a specific location on the basin surface under P waves decreases by approximately 51%, more significant than the decrease under SV waves. The effect of the soil-nonlinearity on the acceleration response spectrums is a decrease of the acceleration amplitude and an increase in the predominant period. Highlights: Seismic response of the 3-D sedimentary basin can be simulated by coupled FEM-IBIEM. Soil-nonlinearity has significant effect on the basin surface response. Central focusing/edge amplification effect occurs with low/high frequency waves. OpenMP + MPI parallel algorithm obviously improves computational efficiency.